The governance of EU fundamental rights - Dawson, Mark (New York: Cambridge University Press, 2017)
"In spite of a continued increase in the substantive scope and reach of EU fundamental rights, little attention has been paid to their practical enforcement. In this book, Mark Dawson looks at the mechanisms through which EU fundamental rights are protected and enforced, closely examining the interrelation between the EU's pertinent legal and political bodies. He argues that in order to understand EU fundamental rights we must also understand the institutional, political and normative constraints that shape the EU's policies. The book examines the performance of different EU institutions in relation to rights and studies two important policy fields - social rights and rule of law protection - in depth"--
"In this book, Mark Dawson looks at the mechanisms through which EU fundamental rights are protected and enforced, closely examining the inter-relation between the EU's pertinent legal and political bodies"--
Machine generated contents note: Introduction; 1. Critiquing and theorising the governance of EU fundamental rights; 2. The Court of Justice in the governance of EU fundamental rights; 3. Fundamental rights and the political institutions; 4. Governing justice and the rule of law; 5. Governing fundamental social rights; 6. Epilogue - accession, asylum and the politics of human rights.
Includes bibliographical references and index.
Keywords: Civil rights -- European Union countries; Social rights -- European Union countries; Political rights -- European Union countries; Law -- European Union countries; LAW / International